Citra Bapak Rumah Tangga dalam Perubahan Nilai dan Keluarga pada Film “I Am Sam” - Rizki Nurcahya; Tresia Robela Yeni; Antiana Nantri; Dahniar TH Musa; Annisa Rizqa Alamri (UIN Fatmawati Sukarno Bengkulu, Indonesia, 2023)
The family is the first place where children learn to be socially oriented, children begin to learn how to respond to the society and adapt in the midst of a wider social life later. The family environment is the main and first growing education center that can influence the development of children both in terms of character, and way of thinking. This research is taken from the movie